Organizational justice and its impact on social organizational behaviours for the Financial Supervision Authority - Bashar Agency - - Moukadem, Djalil; Adnani, Khaoula (Finance and Business Economies Review, 2020)
This study aimed to identify the effect of organizational justice on the social organizational behaviors of the employees of the Financial Supervision Authority and the Bashar Agency. The descriptive analytical method was used to test the study hypotheses, while the data were collected through the use of a questionnaire designed for this purpose. We have identified the study population from the employees of the Financial Supervision Authority, and a sample of (72) employees was selected, where this relationship was tested using the statistical program spss19, and the study concluded that there is a positive impact of organizational justice in its various dimensions on the organizational behavior of the institution under study.